2003
DOI: 10.1044/1092-4388(2003/037)
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Place of Articulation by Children With Cleft Palate and Posterior Placement

Abstract: The aim of this study was to determine if children with repaired cleft palate who demonstrate posterior placement of alveolar targets (e.g., /t h / → [k h ]), known as Group P, differ from children with cleft palate without such an error pattern Group NP) and from normally developing children without cleft palate (Group N) in the perception of /t h / and /k h /. Ten age-matched children in each of these three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(61 citation statements)
references
References 32 publications
2
53
0
6
Order By: Relevance
“…Speech analysis has shown that misarticulations of dental-consonants tended to occur independently of primary palatal surgical technique and timing of palatoplasty and even velopharyngeal function 18 . Additionally, a certain degree of misperception of place of articulation appears to be contributory to the aetiology of speech deficits in cleft patients 23 . On the other hand, OKAZAKI et al 15 have shown that narrower shorter and shallower palates were found particularly in children with misarticulation.…”
mentioning
confidence: 99%
“…Speech analysis has shown that misarticulations of dental-consonants tended to occur independently of primary palatal surgical technique and timing of palatoplasty and even velopharyngeal function 18 . Additionally, a certain degree of misperception of place of articulation appears to be contributory to the aetiology of speech deficits in cleft patients 23 . On the other hand, OKAZAKI et al 15 have shown that narrower shorter and shallower palates were found particularly in children with misarticulation.…”
mentioning
confidence: 99%
“…Conflito de interesses: inexistente ressonância e articulação [1][2][3]5,6 . A hipernasalidade caracteriza-se por ressonância nasal de fones orais, causada pelo fechamento incompleto do esfíncter velofaríngeo 1,3,5,7,8 .…”
Section: Rapid Maxillary Expansion With Haas and The Speech In Peopleunclassified
“…A hipernasalidade caracteriza-se por ressonância nasal de fones orais, causada pelo fechamento incompleto do esfíncter velofaríngeo 1,3,5,7,8 . Fonemas que necessitam de pressão intraoral para serem produzidos, como plosivos e fricativos, ocorrem com emissão nasal, também denominada escape aéreo nasal 1,5,9 .…”
Section: Rapid Maxillary Expansion With Haas and The Speech In Peopleunclassified
See 1 more Smart Citation
“…There is also ample evidence that perception and production are linked in children's phonological acquisition, with a large number of studies reporting that children show specific difficulty discriminating the same contrasts that they neutralize in production (e.g., Hoffman, Daniloff, Bengoa, & Schuckers, 1985; Locke, 1980; McAllister Byun, 2012a; Rvachew & Jamieson, 1989; Velleman, 1988; Whitehill, Francis, & Ching, 2003; Ygual-Fernández & Cervera-Mérida, 2013; but cf. Gierut, 2006).…”
Section: Introductionmentioning
confidence: 99%